The Effect of Implementing a Corporate Resource Management System (ERP) in Improving PT's Supply Chain Management (SCM) Performance. Sat Nusapersada Tbk - Monica, Iveren; Majesty, Shechah; Wang, Devlin; Chrisderry, Chrisderry; Kent, Jeremy (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This research investigates the effect of implementing an Enterprise Resource Management System (ERP) on improving Supply Chain Management (SCM) performance at PT. Sat Nusapersada Tbk. With the research method in the form of interviews, information was obtained from the company owner. The results show that ERP implementation has a significant positive influence on SCM performance at PT. Nusapersada Sat. In facing global competition, SCM is an important key in achieving competitive advantage. ERP helps facilitate a company's internal integration, enabling more effective supply chain management. This study concludes that ERP integration provides significant benefits in increasing company operational efficiency, increasing customer satisfaction, increasing revenue and profits, and optimizing asset use. However, to improve overall SCM performance, wise decision making, effective communication, and good coordination between ERP and SCM are required. Therefore, continuous efforts are needed to improve the system to achieve more optimal results.